TINJAUAN ATAS PROSEDUR PENGAJUAN BIAYA PERJALANAN DINAS DALAM NEGERI PT HUTAMA KARYA (PERSERO) DIVISI PERENCANAAN JALAN TOL - Muhammad Ridwan, (2022)
This Final Project Report which aims to discuss the procedure for filing fees in one of the scopes of state-owned companies, namely the process of official travel activities where when traveling domestically the company has provisions for the SPD implementer in carrying out the official task orders, such as the SPD Executor will get an invitation letter to go on an official trip, then the division leader will issue an assignment letter, then the secretary will make an official travel order (SPPD) to the SPD executor, then the SPD executor will submit a breakdown of the costs to be carried out to carry out domestic official travel duties to the relevant section such as finance who will carry out the preparation of costs, after the cost details have been issued, the SPD executor will carry out the task of the order and will be responsible for the results of the official trip to related parties such as the Executive Vice President (EVP) or Senior Vice President (SVP) and finance to make payments for the detailed costs that have been made in accordance with the provisions that have been applied by the company.